2001
DOI: 10.1093/jnci/93.7.516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Retinoids on Cancerous Phenotype and Apoptosis in Organotypic Cultures of Ovarian Carcinoma

Abstract: At clinically achievable concentrations, all retinoids tested decrease the growth fraction, induce differentiation and apoptosis. Induction of MUC1 expression is implicated in the mechanisms of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 41 publications
2
70
0
Order By: Relevance
“…These concentrations, however, are relevant to short-term (2 -3 days) monolayer culture assays. When the cells are grown within a three-dimensional extracellular matrix in organotypic cultures, and the drugs are administered at 1 Amol/L for 4 days to 2 weeks, both differentiation and apoptosis can be observed within the same cultures (1). What determines if a cell will undergo differentiation or apoptosis in response to 1 Amol/L Flex-Hets has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These concentrations, however, are relevant to short-term (2 -3 days) monolayer culture assays. When the cells are grown within a three-dimensional extracellular matrix in organotypic cultures, and the drugs are administered at 1 Amol/L for 4 days to 2 weeks, both differentiation and apoptosis can be observed within the same cultures (1). What determines if a cell will undergo differentiation or apoptosis in response to 1 Amol/L Flex-Hets has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This objective seems to be met by a novel class of synthetic compounds called flexible heteroarotinoids (Flex-Hets). In vitro studies showed that the Flex-Hets, called SHetA2, SHetA3, and SHetA4, induced differentiation and apoptosis in cancer cell lines and primary cultures of cancer cells (1,2). The Flex-Het compound called SHetA2 was chosen as the lead Flex-Het because it induced the highest levels of apoptosis in multiple cancer types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 While monolayer cultures are suited for evaluation of growth rates, they do not recapitulate interactions with similar and different cell types of cells and with extracellular matrix. We placed the collagen bed at the air-medium interface since it more closely resembles normal ovary structure and discriminates tridimensional growth of normal OSE cells from that of immortalized OSE or malignant ovarian carcinoma lines.…”
Section: Discussionmentioning
confidence: 99%
“…Various synthetic retinoids, including RA, have shown promise for the treatment and prevention of several cancers, including carcinoma of the breast (Veronesi et al, 1999;Dragnev et al, 2000;Guruswamy et al, 2001). Numerous groups, including ours, have found that retinoids potently inhibit the growth of breast cancer cell lines (Zhu et al, 1997;Rosenauer et al, 1998;Wang et al, 2000), and others have reported the capacity of retinoids to inhibit mammary carcinogenesis in animal models (Anzano et al, 1994;Moon and Constantinou, 1997).…”
Section: Introductionmentioning
confidence: 85%